81.8k views
3 votes
Multiply. (2x^2+4x-3)(x^2-2x+5)

1 Answer

1 vote

Explanation:

For a moment let y = x^2 + 5

Then by the distributive property

(2x^2 + 4x - 3 ) P = . 2x^2p + 4xp - 3p

Again by the distributive

2x^2 p = 2x^2(x^2 - 2x +5) = 2x^4 - 4x^3 + 10x^2

4xp = 4x(x^2 + 5) = 4x^3 - 8X^2 +20x

-3p = -3(x^2 - 2x + 5) = -3x^2 + 6x -15

Taking everything together we get

(2x^2 + 4x -3 )(x^2-2x + 5) = (2x^4 -4x^3 +10X^2) + (4x^3 - 8x^2 + 20) + -3x^2 + 6x -15)(2X^2 + 4x - 3 )(x^2 -2x = 5) = 2x^4 + 26 - 15

User AlexZvl
by
5.8k points